UPACARA BERSIH DUSUN NGAGRONG ATAS, DESA NGAGRONG, AMPEL, BOYOLALI SEBUAH STUDI DARI SUDUT SOSIOLOGI SENI - Subandi Subandi (Institut Seni Indonesia Surakarta, 2011)
This research aimed at. finding out a rite using a folk dance. The data were collected using observation, interview and documentation techniques. The data were processed using the technique of qualitative data triangulation consisting of data reduction, data reformation and conclusion. The research result shows that the village purifying ritual is a traditional custom that is still kept alive by the villagers living on the slope of Merbabu mountain. The ritual is held annually on Friday Kliwon on Jumadilakir (the sixth month of the Javanese calendar). A certain performing art is always presented during the ritual. Lembu Sena is one of the folk dances presented as a means of the ritual by Wahyu Budoyo group of art at dusun Ngagrong, Ngagrong Village, Ampel, Boyolali. For the completion of the ritual, an offering is served together with a prayer and its intention. Here acculturation takes place because the ancestor worship is mixed with Islamic beliefs. Traditional Rodhat is presented before the presentation of Lembu Sena dance. And after the presentation of Lembu Sena is over, Rodhat Kalijaga is performed. There are some supporting factors, internal and external ones.Key words: Lembu Sena, ritual, village purifying ritual, acculturation.